DISTRIBUTION AND HIGH ABUNDANCE OF MEDICINAL PLANTS POTENTIALLY USEFUL IN CANCER TREATMENT FOUND ON THE LAWU MOUNTAIN, INDONESIA - Astirin, Okid Parama; Andi Purnomo, Nugroho; Suratman (Indonesian Journal of Forestry Research, 2025)
Traditional medicines derived from natural resource plants have gained attention since modern medications are expensive for certain diseases, including cancer. The Lawu Mountain ecosystem has shown that the environment supports plant distribution, including species with anticancer properties. This study aimed to determine the distribution and abundance of medicinal plants that could serve as cancer preventives, particularly along the Cemoro Sewu hiking trail. The purposive sample method was employed to make the observations, wherein plots measuring 5 m x 5 m for shrubs and 1 m x 1 m for herbs were created. Plots were made by systematic distribution on both sides of the hiking trail, with four plots at each station. This study had six stations at 2,000 m, 2,200 m, 2,400 m, 2,600 m, 2,800 m, and 3,000 m asl. The distribution of plant species was evaluated using the Morishita index distribution, whereas the abundance of species is observed to get the average value in plant individuals per unit area. Depending on the environmental conditions where the growth occurs, the nine species were found along the hiking track with an abundance ranging from 180 to 4,580 individuals per hectare for the shrub category and 5,000 to 50,830 individuals per hectare for the herbaceous category. The distribution patterns of the species were found to be regular and clumped, respectively.